(untitled) (Journal of Advanced Veterinary and Animal Research, 2024)
Objectives: This study aimed to compare the body weight (BW), milk yield, nutritional status, and profitability of moderate genetic (MG) and high genetic (HG) merit of Holstein crossbred (HC) cows in a tropical region under the existing farming system. Materials and Methods: Data was gathered from 204 nursing cows of MG (n = 99) and HG (n = 105) merit of HC cows throughout a year in the dairy zone Keraniganj, Bangladesh. HC cows of MG and HG merit contained 50.0%–67.7% and 75.0%–87.5% Holstein blood, respectively. Data on genetic merit, BW, lactation stage and number, daily milk yield, feed intake, feed, and milk price were documented. All variables were except genetic merit analyzed using one-way analysis of variance. Results: HC cows of MG and HG merit had 433 and 493 kg BW (p < 0.01), and daily produced 11.99 and 14.06 kg milk (p = 0.07) with having 0.99 and 1.15 feed efficiency (p = 0.06), respectively but dry matter intake did not vary (p > 0.05). HC cows of both genetic merit daily offered surplus metabolizable energy and digestible crude protein through roughage and concentrate than their requirement (p > 0.05). The milk production cost of both genetic merit HC cows was alike (p > 0.05), whereas almost two times more profit was obtained in HG merit HC compared to MG merit HC cows (p < 0.05). Conclusion: HC cows of HG merit showed superior potentiality of milk yield, profit, and feed efficiency, whereas MG merit HC cows revealed inferior feed efficiency and milk yield. J. Adv. Vet. Anim. Res., 11(3): 686–692, September 2024 http://doi.org/10.5455/javar.2024.k818